Risk Factors Associated with Prolonged Intensive Care Length of Stay among Coronary Artery Bypass Surgery Patients - Shafira Rahmania; Helda Helda (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Cardiovascular diseases, particularly coronary artery disease (CAD), remain one of the leading causes of global mortality. Coronary Artery Bypass Graft (CABG) surgery is one of the most common treatments for CAD, aiming to reduce morbidity and improve patient quality of life. However, extended stays in the Intensive Care Unit (ICU) post-CABG can negatively affect patient outcomes and increase healthcare resource burdens. This study aims to identify the risk factors that significantly contribute to prolonged ICU stays in post-CABG patients at the National Cardiovascular Center Harapan Kita. A retrospective cohort study was conducted on 4564 patients who underwent CABG surgery between January 2017 and August 2024. Factors such as age, renal failure, stroke, cardiogenic shock, ejection fraction, and use of Intra-Aortic Balloon Pump (IABP) were analyzed. Bivariate analysis was performed using Stata 15.1 version through the Chi-square test, resulting in P-Value and Confidence Interval, and followed by multivariate logistic regression to determine significant predictors. Among the patients, 747 (16.3%) experienced prolonged ICU stays (≥72 hours). Significant risk factors for prolonged ICU stay included age ≥59 years (OR 1.43, 95% CI 1.16-1.71), history of renal failure (OR 2.39, 95% CI 1.74-3.28), preoperative stroke (OR 1.85, 95% CI 1.38-2.48), cardiogenic shock (OR 13.9, 95% CI 5.42-35.64), low ejection fraction (OR 2.66, 95% CI 1.33-3.73), and IABP use (OR 36.34, 95% CI 26.20-50.40). This study showed that there are several risk factors such as age, history of renal failure, preoperative stroke, cardiogenic shock, low ejection fraction, and IABP usage which needs attention to produce better outcome, especially for ICU stay in isolated CABG patients in Indonesia. Keyword: CABG, Intensive Care, Prolonged Stay, Risk Factors